(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
This research targets to analyses and evaluates some productive and technological characteristics of Khdairy variety of olive (Olea europaea L.) in order to select the best phenotypes for Propagation, and genetic improvement program. This work was carried out during the years 2015 and 2016. Fifteen phenotypes were collected from 5 sites in Lattakia (Bouka, Mashkita, Ein albaida, Alkanjra and Jannata). The evaluation included five characteristics, two of them were productive traits (Fruit production and oil content) and three were technological traits (fruits weight, stone weigth and reflux %). Data were subjected to ANOVA analysis to compare the averages at a significant level of 5%. Phenotypes SN2 and SN3 showed the highest values of oil percentage, reaching 29.42% and 29.61%, respectively. No significant difference for tree production was detected between olive phenotypes, although all phenotypes produced good fruit yield comparing to reference values. For technological traits, the fruits weight ranged between small and medium (from 1.8g in BO2 to 3.13g in BC3), and fruits from phenotypes BC3 and BC2 were significantly bigger than the rest of genotypes. The 15 olive phenotypes possessed medium-sized stones, and reflux percentage ranged between 73.49% (in BO2) and 86.25% (in BO1). هدف هذا البحث لتحليل وتقييم بعض الصفات الإنتاجية والتكنولوجية لطرز من الزيتون الخضيري في محافظة اللاذقية وانتخاب الطرز المميزة بغية إكثارها والاستفادة منها في برامج التربية والتحسين الوراثي. نفذ البحث خلال الموسمين 2015 و2016 على 15 طرازاً من الصنف الخضيري تتبع للنوع Olea europaea .L. جمعت العينات من خمسة مواقع في محافظة اللاذقية هي بوقا، مشقيتا، عين البيضا، القنجرة، جناتا. قيمت الطرز المختارة من الناحية الإنتاجية (إنتاج الشجرة من الثمار، والنسبة المئوية للزيت)، ومن الناحية التكنولوجية (وزن الثمرة، وزن النواة، نسبة التصافي)، وأخضعت النتائج لتحليل التباين ANOVA لمقارنة المتوسطات عند مستوى معنوية 5%. تباينت الطرز المختبرة بنسبة الزيت فيها، وتفوق الطرازان SN3(29.61%) و SN2 (29.42) على الطرز الأخرى، في حين لم تكن الفروق معنوية بين الطرز المدروسة من حيث متوسط انتاجها من الثمار، علماً بأن جميعها تميز بإنتاج جيد مقارنة بالنسب المرجعية. أما بالنسبة للصفات التكنولوجية، فقد تميزت ثمار الطرز المدروسة بكونها صغيرة إلى متوسطة الوزن (بين 1.8غ عند الطراز BO2 و3.13غ عند الطراز (BC3 و تفوق الطرازان BC2, BC3 معنوياً بوزن الثمرة على الطرز الأخرى، وكذلك بامتلاك جميع الطرز لنوىً متوسطة الوزن ولنسبة تصافٍ تراوحت بين 73.49% (عند BO2) و 86.25 % (عند BO1).